Exploring factors contributing to adolescent suicide using psychological autopsy - A scoping review - Josna Soyuz; Teddy Andrews Jaihind Jothikaran; K. K. Sakkir; Anish V. Cherian; Lena Ashok; Varalakshmi Chandrasekaran; Boby Augustin; S. Elstin Anbu Raj (PLoS ONE, 2026)
Background Adolescent suicidality and associated behaviours are an alarming global public health concern. Understanding its underlying causes and trajectories necessitates the urgent development of targeted prevention strategies. Psychological autopsy (PA) methods provide an in-depth understanding of the complex risk factors leading to suicide in this vulnerable population. Objective This scoping review aims to explore and synthesise the major risk elements contributing to adolescent suicide and to propose a synthesis of the trajectories leading to adolescent suicide. Methods A methodological search was carried out to find psychological autopsy studies centered on adolescent subjects. The selection criteria were fulfilled by 15 papers, which were scrutinized with the help of a thematic synthesis method and extracted the main themes to create an overview of the scope and character of the risk factors found. Results Four major themes emerged: (1) Individual risk factors, including psychiatric disorders, substance use, and previous self-harm; (2) Familial factors, such as parental mental illness, abuse, neglect, and family dysfunction; (3) Life events, including academic failure, interpersonal conflicts, and childhood trauma and (4) Environmental risk factors, such as access to lethal means, media influence, and lack of mental health support. The findings highlight the complex interplay of psychological, social, and contextual variables in adolescent suicide. Conclusion Psychological autopsy studies offer valuable insights into the risk factors for adolescent suicide. A multidimensional approach addressing individual vulnerabilities, family dynamics, and broader social environments is essential for effective prevention efforts. Further research is needed to strengthen the evidence base and guide policy and intervention development.